Efficient Design Method of Segmented Lenses for Lighting Applications with Prescribed Intensity and Low Peak Luminance. Issue 4 (2nd October 2019) - Desnijder, Karel; Deketelaere, Ward; Ryckaert, Wouter; Hanselaer, Peter; Meuret, Youri
ABSTRACT: Light emitting diodes (LEDs) that are used today in general lighting applications provide high luminous flux from small packages, which can result in high peak luminance and glare. The use of diffusors allows reducing peak luminances, but these components do not allow accurate control over the resulting intensity pattern as is possible with nonimaging lenses for low- étendue sources such as LEDs. In this article, a new design method is presented to create a rotational or transverse symmetric segmented lens that results in a reduced peak luminance but still allows excellent control over the resulting intensity distribution. Each segment of the lens spreads out the light in a certain angular range, but the different contributions of each lens segment result together in the desired target intensity distribution. The design method is based on the iterative optimization of a linear transformation of a source intensity distribution into a target intensity distribution, starting from a transformation that yields maximal light beam spreading.